JENIS DAN POPULASI SERANGGA DI AREAL TANAMAN NENAS (Ananas Comosus (L.) Merr.) KECAMATAN PASSI BARAT KABUPATEN BOLAANG MONGONDOW - Slamet Pulukadang; Juliet M.E. Mamahit; Moulwy F. Dien; Guntur S.J. Manengkey (COCOS, 2014)
ABSTRACTThis study aims to determine the insect types and populations at the areas of Pineapple plants near housing ecosystems and near forest ecosystems. The experiment was conducted in centers of Pineapple plantation in the Mongkonai and Lobong village District of Bolaang Mongondow and at the Laboratory of Entomology and Plant Pests UNSRAT Faculty of Agriculture for five months from July to December. insect Observation on pineapple plants is done by using the method of trapping wells (pithfall) on generative plant and samples insects taken three times. The results showed that there are four associated insect Order on the areas of Pineapple plants near housing ecosystems are: Order Orthoptera (Family Acrididae, Gryllidae); Order Coleoptera (Family Scolytidae, Scarabaiedae); Order Diptera (Family Drosophilidae, Bombyliidae); and the Order Hymenoptera (Family Formicidae), while on the area of Pineapple planting near the forest ecosystem there are five insects Order are :: Order Orthoptera (Family Gryllidae, Acrididae, and Blattidae); Order Coleoptera (Family Scarabaeidae, Scolytidae, Cicindelidae, Crysomelidae, and Alleculidae); Order Diptera (Family Drosophilidae, Bombyliidae, and Tachinidae); Order Hymenoptera (Family Formicidae); and the Order Lepidoptera (Family Pyralidae). The results also obtain the number of insects found in varying amounts each Family. The number of insects found on average ranges from 2-423 insect.Key words : the insect types and populations, Pineapple plants